2020
DOI: 10.1017/cha.2020.41
|View full text |Cite
|
Sign up to set email alerts
|

Zimbabwe’s poverty and child sexual abuse

Abstract: Child sexual abuse (CSA) is a serious scourge that affects all countries globally. While there are myriad factors contributing the prevalence of CSA in Zimbabwe, poverty is arguably one of the major underlying issues and root causes of most of these factors. Over the past two decades, Zimbabwe has gone through an unprecedented economic meltdown; fewer resources are being channelled towards child protection leading to the decline in standards of living for children. Consequently, children are left vulnerable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Mtetwa and Muchacha (2013) recommend safeguarding the rights of the most vulnerable by taking an interest in the political situation of the communities in which they work. Muridzo and Chikadzi (2020) argue that social work should involve itself with global, regional, and local policy issues as this will help address casual factors. Mupedziswa (2000) argues that this starts in the classroom and literature used in training social workers in the continent.…”
Section: Discussionmentioning
confidence: 99%
“…Mtetwa and Muchacha (2013) recommend safeguarding the rights of the most vulnerable by taking an interest in the political situation of the communities in which they work. Muridzo and Chikadzi (2020) argue that social work should involve itself with global, regional, and local policy issues as this will help address casual factors. Mupedziswa (2000) argues that this starts in the classroom and literature used in training social workers in the continent.…”
Section: Discussionmentioning
confidence: 99%
“…Badoe, 2017;Banwari, 2011;Nlewem & Amodu, 2017). Within the scientific discourse, single parental absence and absence of both parents are associated with the experience of sexual violence victimisation in adolescent girls (Kidman & Palermo, 2016;Muridzo & Chikadzi, 2020). When the absent parent is paternal, challenges related to family poverty, financial difficulties and food supply are pronounced.…”
Section: Survivor Characteristicsmentioning
confidence: 99%
“…However, maternally related absence is usually linked with a loss of nurturing, support and companion for the children (Kidman & Palermo, 2016). Research has shown a strong relationship between poverty and sexual crimes (Banwari, 2011;Muridzo & Chikadzi, 2020). Families experiencing poverty are likely to live in a deprived community, and children and adolescents who find themselves in such situations experience less parental supervision, lack of financial support and are at an elevated risk of involvement in child labour (Wrigley-Asante et al, 2016).…”
Section: Survivor Characteristicsmentioning
confidence: 99%